Artificial molecular-level machines with [Ru(bpy)3]2+ as a "light-fueled motor". (2001) - Ballardini, Roberto; Balzani, Vincenzo; Credi, Alberto; Gandolfi, Maria Teresa; Venturi, Margherita
Abstract : A molecular-level machine is an assembly of a discrete number of molecular components (that is, a supramolecular structure) designed to perform mechanical-like movements (output) as a consequence of appropriate external stimuli (input). Like macroscopic machines, molecular-level machines are characterized by (i) the kind of energy input supplied to make them work, (ii) the kind of movement performed by their components, (iii) the way in which their operation can be controlled and monitored, (iv) the possibility to repeat the operation at will and establish a cyclic process, (v) the time scale needed to complete a cycle of operation, and (vi) the function performed. The most convenient way to supply energy to an artificial molecular-level machine is through a photochemical reaction.[ Ru ( bpy ) 3 ] 2 + (bpy = 2, 2 ′ -bipyridine) can be used as a photosensitizer to power mechanical movements in machines based on pseudorotaxanes, rotaxanes and catenanes. Besides being used as an external photosensitizer, [ Ru ( bpy ) 3 ] 2 + can be incorporated in one of the machine components as a "light-fueled" motor. Three types of photochemically driven piston/cylinder systems and a photocontrollable molecular abacus are described. Other kinds of more sophisticated molecular-level machines based on rotaxanes and catenanes are proposed. The extension of the concept of machine to the molecular level is important not only for the sake of basic research, but also for the growth of nanoscience and the development of nanotechnology.